Znaczenie szacowania wartości klienta w osiąganiu sukcesu rynkowego przedsiębiorstwa - Pukas, Anetta (The role of customer equity estimation in achievement of company market success, 2006)
The last decade has seen significant interest in a new model of enhancing the performance and competitiveness of businesses by directly managing the firm's customer equity. Customer Relationship Management System (CRM) helps companies unlock the full value of their relationship assets, accelerating revenue and profit growth. This paper discusses how firms should measure this processes and activity to improve their market position.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 280-285